Chemo-enzymatic epoxidation of sunflower oil methyl esters - Schneider,Rosana de Cassia S.; Lara,Luciano R. S.; Bitencourt,Thiago B.; Nascimento,Maria da Graça; Nunes,Marta R. dos Santos (Sociedade Brasileira de Química, 2009)
The chemo-enzymatic epoxidation of the methyl esters of sunflower oil with lipase from Candida antarctica B and aqueous H2O2 in the presence and absence of an acyl donor was investigated. The biphasic system (CH2Cl2/H2O) comprised Candida antarctica B lipase (CALB, 1000 u g-1) and 30% (v/v) aqueous hydrogen peroxide. In some cases the conversion was higher than 99%. The best results were obtained for the biphasic system after 16 h of reaction, at 30 ºC, using 10 mmol of octanoic acid in relation to 1 g of the oil, 6 mL of dichlomethane and 5 mL of water.